Application of glutathione depletion in cancer therapy: Enhanced ROS-based therapy, ferroptosis, and chemotherapy - Niu, Boyi; Liao, Kaixin; Zhou, Yixian; Wen, Ting; Quan, Guilan; Pan, Xin; Wu, Chuanbin (Biomaterials, 2021)
Glutathione (GSH) is an important member of cellular antioxidative system. In cancer cells, a high level of GSH is indispensable to scavenge excessive reactive oxygen species (ROS) and detoxify xenobiotics, which make it a potential target for cancer therapy. Plenty of studies have shown that loss of intracellular GSH makes cancer cells more susceptible to oxidative stress and chemotherapeutic agents. GSH depletion has been proved to improve the therapeutic efficacy of ROS-based therapy (photodynamic therapy, sonodynamic therapy, and chemodynamic therapy), ferroptosis, and chemotherapy. In this review, various strategies for GSH depletion used in cancer therapy are comprehensively summarized and discussed. First, the functions of GSH in cancer cells are analyzed to elucidate the necessity of GSH depletion in cancer therapy. Then, the synthesis and metabolism of GSH are briefly introduced to bring up some crucial targets for GSH modulation. Finally, different approaches to GSH depletion in the literature are classified and discussed in detail according to their mechanisms. Particularly, functional materials with GSH-consuming ability based on nanotechnology are elaborated due to their unique advantages and potentials. This review presents the ingenious application of GSH-depleting strategy in cancer therapy for improving the outcomes of various therapeutic regimens, which may provide useful guidance for designing intelligent drug delivery system.